A study on evolutionary optimization for the channel optimization problem in wireless mobile network - Tze, Kenneth Kin Teo; Mohd. Sigit Arifianto; Liau, Chung Fan; Liawas Barukang; Razak Mohd Ali Lee; Chia, Yee Shin (Universiti Malaysia Sabah, 2007)
The channel assignment problem in wireless mobile network is to assign appropriate frcqucnc)' spectrum channels to requested calls while satisfying the electromagnetic compatibility (EMC) constraint. However with the limited capacity of wireless mobile frequency spectrum, an effective channel assignment technique is important for resource management and to reduce the effect of interference. Most of the existing channel assignment techniques are based on deterministic methods. In this research, an adaptive channel assignment technique based on genetic algorithm (GA) is introduced. The most significant advantage of GA based optimization in channel assignment problem is its capability to handle both the reassignment of existing calls as well as the allocation of channel to new call in an adaptive process to maximize the utility of the limited resources. The population size is adapted to the number of eligible channels for a particular cell upon new call arrivals in order to achieve reasonable convergence speed. The MA TlAB simulation on a 49-cells network model for both uniform and nonuniform traffic demands showed that the average new incoming call blocking probability for the proposed channel optimization method is lower than the deterministic channel assignment methods.